Scalability analysis of low-power wide area network technology - Yusoff, M.H.; Abdul Latiff, N.A.; Ismail, I.S.; Yusoff, M.H.; Salisa, A.R.; Shukor, J.A. (2021)
Low-power wide area network is a new wireless communication technology designed for low-power consumption together with long-distance communications, and LoRa technology is one of the leading technology solutions. The long-range connection between end-nodes and gateway is achievable by LoRa devices due to star-based network topology and modulation techniques used in wireless communication of the technology. One of the main features of LoRa technology is the ability to scale. Modelling and simulation can interpret the actual network behaviour of LoRa technology as accurate as possible. This paper aims to investigate the performance of the low-power wide area network technology focusing on capability of the network to scale. We model the network system based on the behaviours of the communication between the end-node and gateway. The simulation to study the scalability was done based on several parameters, such as the number of end-nodes, application time and the number of channels used by the end-node. The results show that the amount of successfully received data signal at gateway increased as the application time and channel used increased.